'Co-evolution' of uranium concentration and oxygen stable isotope in phosphate rocks. (March 2020) - Sun, Y.; Amelung, W.; Wu, B.; Haneklaus, S.; Maekawa, M.; Lücke, A.; Schnug, E.; Bol, R.
Abstract: Phosphate rocks (PRs) used in fertilizer production contain uranium (U), which enters agricultural soils through phosphorus fertilization. However, our knowledge is still limited and cannot explain the different levels of U contamination found in agricultural systems. The paper reviewed the spatial and temporal U variations in PRs to obtain a comprehensive overview of U levels in various PRs worldwide and to investigate why U concentrations in igneous PRs are significantly lower compared to sedimentary PRs, and why less U is present in old sedimentary PRs (Precambrian-Cambrian) than in younger PRs (Ordovician-Neogene). In addition, the natural oxygen isotope compositions of phosphate (δ 18 Op ) in various PRs were determined to identify their origins in relation to their U concentration. The δ 18 Op values differed among igneous PRs, old sedimentary PRs, and younger sedimentary PRs. Generally, the PRs with low δ 18 Op values had low U concentrations. In igneous PRs, low U concentrations were due to the lack of secondary U enrichment processes after rock formation, with low δ 18 Op values resulting from limited isotope fractionation at high temperature. Conversely, in sedimentary PRs, both U concentrations and δ 18 Op values were influenced by paleoclimate and paleogeographic features. Overall, there is a time-dependent coincidence of processes altering U concentration and δ 18 Op signatures of sedimentary PRs in a similar direction. Highlights: The U contents of phosphate rocks (PRs) increase in the order: igneous PRs, old sedimentary PRs (Precambrian-Cambrian), younger sedimentary PRs (Ordovician-Neogene). The values of δ 18 Op of PRs increase as follows: igneous PRs, old sedimentary PRs (Precambrian-Cambrian), younger sedimentary PRs (Ordovician-Neogene). In sedimentary PRs, there is a time-dependent coincidence of processes altering U concentration and δ 18 Op signatures in a similar direction.